Pesticides and public health: discussing risks in Brazilian agro-industrial growth - Perobelli, Juliana E. (Frontiers in Toxicology, 2025)
The benefits of pesticides in enhancing agricultural yields are widely accepted by the general public. However, it is essential to address the limitations of the current agricultural model to develop more sustainable practices that prioritize environmental and human health. Brazil, a major global agricultural player, ranks among the top five agro-food producers and exporters, making it one of the largest consumers of pesticides worldwide. Notably, approximately 30% of pesticides used in Brazil are banned in the European Union. Paradoxically, some of these banned agrochemicals re-enter Northern markets through imported agro-food products. Addressing the regulatory disparities between Northern and Southern countries necessitates global initiatives and research to better understand the real biological risks associated with pesticide exposure, particularly concerning reproductive health, endocrine disruption, and carcinogenesis—key targets of these chemicals. Since 2001, the Brazilian Health Regulatory Agency (ANVISA) has operated the “Reports on Pesticide Residue Analysis in Food (RPRAF)” program to evaluate pesticide residues in food samples collected across Brazil. Despite its limitations, the program has been crucial in identifying the chemical exposome related to Brazilian agro-foods, facilitating studies on relevant pesticides, their doses, routes, and exposure schedules, and enabling the development of pre-clinical studies based on real-life exposure scenarios. A thorough understanding of the main mechanism of toxicity is crucial for raising awareness about the health risks associated with pesticide exposure, fostering tailored health strategies and guiding informed regulatory policies.